Pengelolaan Zakat Produktif Dalam Meningkatkan Kesejahteraan Umat - Muhammad Dzaki Hawari; Muhammad Zen (Jurnal Manajemen Dakwah, 2020)
Productive Zakat management to improve the welfare of the people is carried out by the management and staff of the Indonesian Zakat House amil zakat institution, to maintain its existence as an NGO-based social institution (Non-Government Organization), the quality of management is an important essence in serving donors in general and in particular. the mustahik in the village are empowered so that the collection and distribution process is in accordance with the wishes of the donors and mustahik who are worthy of welfare. This research was conducted to carefully study the implementation of productive zakat management carried out by Rumah Zakat Indonesia with the aim of improving the welfare of the people. Management of services in terms of collection, data collection of donors, data collection of mustahik, improving the quality of amil to the stage of distributing zakat funds according to the institution's program. This study uses descriptive qualitative methods, namely using the method of observation and interviews as the author's research instruments. Based on the results of the author's research, it was found that the management of zakat funds in Rumah Zakat institutions is quite good which can improve the welfare of the people. Starting from raising funds to the stage of distribution, God willing, it is right on target according to the alquran and hadith. Pengelolaan Zakat Produktif untuk meningkatkan kesejahteraan umat dilakukan oleh para pengurus dan staff amil zakat lembaga Rumah Zakat Indonesia, untuk tetap mempertahankan eksistensinya sebagai lembaga sosial yang berbasis NGO (Non Government Organization), kualitas pengelolaan merupakan suatu esensi yang penting dalam melayani donatur pada umumnya dan khususnya para mustahik yang ada di desa berdaya agar proses penghimpunan dan penyaluran sesuai dengan keinginian donatur dan mustahik yang layak untuk disejahterakan. Penelitian ini dilakukan untuk mempelajari secara seksama implementasi pengelolaan zakat produktif yang dilakukan oleh Rumah Zakat Indonesia dengan tujuan meningkatkan kesejahteraan umat. Pengelolaan pelayanan dari segi penghimpunan, pendataan donatur, pendataan mustahik, meningkatkan kualitas para amil sampai pada tahap penyaluran dana zakat sesuai dengan program lembaga. Penelitian ini menggunakan metode kualitatif deskriptif yakni menggunakan metode observasi dan wawancara sebagai instrument penelitian penulis.Berdasarkan hasil penelitian penulis, ditemukan pengelolaan dana zakat di lembaga Rumah Zakat yang cukup baik yang mampu meningkatkan kesejahteraan umat. Mulai dari penghimpunan dana sampai pada tahap penyaluran yang insya Allah tepat sasaran sesuai dengan alqur’an dan hadits.